Impact of Natural Born Leader Qualities on the Project Team Performance: The Influences of Demographics (Gender and Age) - Saif ul Amin; Yasir Kamal (International Journal of Management, Accounting and Economics, 2016)
This paper examines the impact of nature born leader qualities on project team performance. This research also studies the influence of demographic factors (age, and gender) on the impacts of a nature born leader qualities intention in projects perspective. A quantitative technique was adopted in this research. Data were collected through questionnaire survey from Pakistani project. Questionnaire form covered all variables and collected data analyzed through SPSS. Regression Analysis and Wilcoxon matched-pairs signed-rank tests were applied to test the hypothesis and make inference from the collected data. Statistical analysis revealed the impact of natural born leader qualities on both subjective and objective performance of project teams. Finding also supported the proposed hypotheses about influences of demographic variables. The findings address a number of weaknesses in literature by providing statistical evidence of the influence demographic characteristics. The findings can thus help theoretically; and practically to project manager by understanding the conflict resolution of different age and gender of their followers. This research also benefit for the research scholar engaged in pursuing literature on leadership behavior, project management and performance.